Modeling of limitations on the use of hydraulic motor-wheels in transmissions of mobile machines - Avrunin, G.; Podrigalo, M.; Podrigalo, N.; Fidrovskaya, N.; Moroz, I.; Yatsunskyi, P.; Аврунін, Г. А.; Подригало, М. А.; Подригало, Н. М.; Фідровська, Н. М.; Мороз, І. І.; Яцунський, П. П. (Харківський національний автомобільно-дорожній університет, 2024)
Problem. The development of mobile machines with increased movement speeds requires constructive solutions for the creation of appropriate transmissions, particularly the analysis of the possibility of creating hydraulic stepless transmissions using hydraulic motors of various types. Goal. Increasing the technical level of transmissions of utility, construction and road vehicles and multi-axle high-speed vehicles with the help of advances in modern hydrostatic transmissions. Methodology. The transmissions of mobile machines are considered from the point of view of the possibility of using multi-cycle radial-piston hydraulic motors in them as gearless hydraulic motor-wheels. According to the traction-speed characteristics, the values of the torques and rotation frequencies of the hubs were calculated, and the hydraulic motor-wheels were selected according to the corresponding working volumes. As an example, calculations of the dynamics of the hydraulic drive transmission of a cleaning utility vehicle were carried out using the VisSim application program package, where the universal characteristic of the gerotor hydraulic motor was used to determine the hydromechanical efficiency in the modes from displacement to maximum rotation frequency. The results. Positive results were obtained in terms of increasing the speed of mobile machines when using hydraulic motor-wheels of radial piston multicycle action in transmissions instead of gerotor hydraulic motors, axial-piston hydraulic motors with planetary gearboxes, hydraulic transmissions with cardan shafts and mechanical transmissions. Originality. New calculated data on the initial characteristics of transmissions with a hydraulic drive were obtained, the possibilities of modeling dynamic processes in the transmission hydraulic drive depending on the action of external factors regarding the load, speed and properties of the working fluid were shown. It was established that for multi-axle vehicles with a maximum speed of up to 100 km/h, the use of electric or hydraulic motor-wheels requires the addition of planetary gearboxes with reducers or multiplier frames. Practical meaning. Recommendations for the use of radial-piston gearless hydraulic motor-wheels in mobile machines in order to improve their technical level are given.
Моделювання обмежень щодо застосування гідромотор-колес в трансмісіях мобільних машин
Keywords: vehicle; transmission; hydraulic motor-wheel; torque; rotation frequency; dynamic calculations; VisSim package; транспортний засіб; трансмісія; гідромотор-колесо; крутний момент; частота обертання; динамічні розрахунки; пакет VisSim; 629.225; 10.30977/AT.2219-8342.2024.55.0.05